Food deprivation differentially modulates gene expression of LPXRFa and kisspeptin systems in the brain-pituitary axis of half-smooth tongue sole (Cynoglossus semilaevis) - Wang, Bin; Cui, Aijun; Xu, Yongjiang; Zhang, Yaxing; Jiang, Yan; Liu, Xuezhou (Frontiers in Endocrinology, 2023)
LPXRFa, also known as gonadotropin-inhibitory hormone (GnIH), and kisspeptin (Kiss) are two major hypothalamic peptides that modulate the reproductive axis of vertebrates, including teleosts. However, little information is available regarding the actions of nutritional status on the regulation of these two neuroendocrine systems in fish. Herein, we assessed the effects of starvation and refeeding on the expression of lpxrfa, kiss2 and their receptors (lpxrfa-r and kiss2r respectively) at the brain-pituitary level of half-smooth tongue sole (Cynoglossus semilaevis). Food deprivation for 4 weeks induced a rise in brain lpxrfa as well as brain and pituitary lpxrfa-r mRNA levels, and refeeding restored brain lpxrfa and lpxrfa-r expression back to normal. However, pituitary lpxrfa-r mRNA levels still remained high after 1 week of refeeding. Neither lpxrfa nor kiss2 transcripts in the pituitary were altered by fasting, but their mRNA levels increased significantly after 1 week of refeeding, and declined back to the control levels after 2 weeks of refeeding. None of brain kiss2 and kiss2r along with pituitary kiss2r transcripts were modified by the nutritional status. In summary, our results revealed an interaction between energy status and the elements of LPXRFa and Kiss systems in the brain-pituitary axis of half-smooth tongue sole. Food deprivation and refeeding differentially regulated the two systems, which provided additional evidence for the involvement of the LPXRFa and Kiss systems in the regulation of reproduction by energy balance in non-mammalian species.